The sound of silence: Blank spaces, fading narratives and fragile frames in comics. Issue 2 (1st November 2019) - Sanyal, Debarghya
AbstractHow does one translate silence onto a silent medium? Printed comic books and graphic novels are generally a non-auditory art form. This has caused them to be traditionally perceived as 'silent'. This also means that comics artists have come up with some of the most innovative ways of translating sound to a primarily visual medium ‐ bold letters, onomatopoeic words, fading images, etc. Nonetheless, these innovations have often in fact failed to address silence. As an art form where both the blank space and the printed word acquire their own unique visual signification, is comics rather a stubbornly un-silent medium? If so, then how does one depict silence in an un-silent medium? My article addresses these questions by first examining the works of Scott McCloud, Thierry Groensteen and Barbara Postema and their study of sound in comics. I then build on these theoretical frameworks to problematize the conventional correlation of visual signifiers with sound and silence, primarily examining the use of blank space or the lack of words as a default signifier of silence. Ultimately, I will argue that comic books provide a unique transmedial approach to re-analyse our conventional ideas for visual representations of sound.